Study of β-Ga2O3 Ceramics Synthesized under Powerful Electron Beam - Usseinov, Abay B.; Karipbayev, Zhakyp T.; Purans, Juris; Kakimov, Askhat B.; Bakytkyzy, Aizat; Zhunusbekov, Amangeldy M.; Koketai, Temirgali A.; Kozlovskyi, Artem L.; Suchikova, Yana; Popov, Anatoli I. (MDPI, 2023)
The synthesis of β-Ga2O3 ceramic was achieved using high-energy electron beams for the first time. The irradiation of gallium oxide powder in a copper crucible using a 1.4 MeV electron beam resulted in a monolithic ceramic structure, eliminating powder particles and imperfections. The synthesized β-Ga2O3 ceramic exhibited a close-to-ideal composition of O/Ga in a 3:2 ratio. X-ray diffraction analysis confirmed a monoclinic structure (space group C2/m) that matched the reference diagram before and after annealing. Photoluminescence spectra revealed multiple luminescence peaks at blue (~2.7 eV) and UV (3.3, 3.4, 3.8 eV) wavelengths for the synthesized ceramic and commercial crystals. Raman spectroscopy confirmed the bonding modes in the synthesized ceramic. The electron beam-assisted method offers a rapid and cost-effective approach for β-Ga2O3 ceramic production without requiring additional equipment or complex manipulations. This method holds promise for fabricating refractory ceramics with high melting points, both doped and undoped. --//-- This is an open access article Usseinov, A.B.; Karipbayev, Z.T.; Purans, J.; Kakimov, A.B.; Bakytkyzy, A.; Zhunusbekov, A.M.; Koketai, T.A.; Kozlovskyi, A.L.; Suchikova, Y.; Popov, A.I. Study of β-Ga2O3 Ceramics Synthesized under Powerful Electron Beam. Materials 2023, 16, 6997. https://doi.org/10.3390/ma16216997 published under the CC BY 4.0 licence.
This research has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14870696). Financial support in Latvia was provided by ERAF Project Nr. 1.1.1.1/20/A/057. In addition, J.P and A.I.P. thank the Institute of Solid State Physics, University of Latvia (ISSP UL). ISSP UL as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; synthesis; power electronic flux; β-Ga2O3 ceramics; photoluminescence; annealing; point defects